2020
DOI: 10.1001/jamadermatol.2020.2127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Treatment Outcomes of Persistent Radiation-Induced Alopecia in Patients With Cancer

Abstract: IMPORTANCE Persistent radiation-induced alopecia (pRIA) and its management have not been systematically described.OBJECTIVE To characterize pRIA in patients with primary central nervous system (CNS) tumors or head and neck sarcoma. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study of patients from January 1, 2011, to January 30, 2019, was conducted at 2 large tertiary care hospitals and comprehensive cancer centers. Seventy-one children and adults diagnosed with primary CNS tumors or head and neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…5 Both the cumulative dose and the fractional dose used are important in causing alopecia with radiotherapy. 9 Our experience indicates that the radiation dose needed to permanently kill hair and eliminate the disease in inflamed and friable AKN lesions is less than the dose required for noninflamed areas of the scalp.…”
Section: Discussionmentioning
confidence: 89%
“…5 Both the cumulative dose and the fractional dose used are important in causing alopecia with radiotherapy. 9 Our experience indicates that the radiation dose needed to permanently kill hair and eliminate the disease in inflamed and friable AKN lesions is less than the dose required for noninflamed areas of the scalp.…”
Section: Discussionmentioning
confidence: 89%
“…Patchy alopecia is the most commonly observed pattern following radiation. 12 It leads to huge cosmetic disfigurement.…”
Section: Discussionmentioning
confidence: 99%
“…They have proven association with alopecia, neurocognitive dysfunction, and memory loss and that can have a profound impact on the patient's quality of life. [4][5][6] This raises the importance of taking into account these structures as additional OAR's in radiation planning along with other routine serial structures.…”
Section: Introductionmentioning
confidence: 99%
“…In patients experiencing chronic radiation alopecia, one study found that topical minoxidil 5% BID improved hair regrowth in 82% of patients and given its favorable safety profile, is a reasonable option for interested patients (35). Patients with significant chronic alopecia can also be referred for hair prosthesis.…”
Section: Alopecia and Dermatitismentioning
confidence: 99%